Accelerated multi-property discovery of promising Fe-Si-Al magnetic alloys - Tsakadze, Zviad (2025)
Fe-Si binary alloys are one of the most widely used magnetic materials, while some ternary Fe-Si-Al alloys also have excellent magnetic properties and high electrical resistivity. However, none of these alloy compositions meet the multiple superior properties needed in next generation electrical motors. Hence, there is an urgent need to identify novel Fe-Si-Al alloy compositions with a good property set. Compositionally graded materials libraries of Fe-xSi-yAl (x = 3, 7, 9; 0 ≤ y ≤ 8, in wt%) were prepared by mechanical alloying and high throughput spark plasma sintering. The structural, magnetic, mechanical, and electrical properties were rapidly assessed and found to vary significantly with composition. Four promising compositions were down selected based on rapid characterization and property evaluation of the materials libraries. Validation studies of these compositions revealed that the Fe-7Si-8Al composition exhibited an attractive combination of properties. Thus, an accelerated methodology was used to discover new attractive alloy compositions for rotating electrical machines.